Odpowiedzi

2009-11-20T19:09:47+01:00
1)
2x-4*5x=18
-18x=18
x=-1
2)
3x+6y=12
x=-3y
-9y+6y=12
-3Y=12
y= -4
3)-3x+2y=1
x-y=3 x=3+y

-3(3+y)+2y=1
-9+3y=1
3y=10
y=3,333...

4)x+y=9
x-y=-1 x=-1+y
-1+y+y=9
2y=8
y=4

5)
x+y=8
x-y=0 x=y
2y=8
y=4
2009-11-20T19:09:56+01:00
A) 2x-4y=18
y=5x

2x-4*5x=18
2x-20x=18
-18x=18

x=-1
y=5x=-5

b) 3x+6y=12
x=-3y

3*-3y+6y=12
-9y+6y=12
-3y=12
y=-4
x=-3y

y=-4
x=-4(-3)=12

c) -3x+2y=1
x-y=3

-3x+2y=1
x=y+3

-3(y+3)+2y=1
-3y-9+2y=1
-y=10
y=-10

x=y+3

y=-10
x=-7

d) x+y=9
x-y=-1

x+y=9
x=-1+y

=1+y+y=9
2y=8
y=4

x+y=9
x=9-y
x=9-4
x=5
y=4

d) x+y=8
x-y=0

x=8-y
x-y=0

8-y-y=0
8=2y
y=4

y=4
x-y=0

x-4=0
x=4
2009-11-20T19:44:02+01:00
A) 2x-4y=18
y=5x

2x-4(5x)=18
y=5x

2x-20x=18
y=5x

-18x=18/:(-18)
y=5x

x=-1
y=-5

B) 3x+6y=12
x=-3y

3(-3y)+6y=12
x=-3y

-9y+6y=12
x=-3y

-3y=12/:9(-3)
x=-3y

y=-4
x=-3*(-4)

y=-4
x=-12

C)-3x+2y=1
x-y=3

-3x+2y=1
x=3+y

-3(3+y)+2y=1
x=3+y

-9-3y+2y=1
x=3+y

-y=1+9
x=3+y

-y=10/*(-1)
x=3+y

y=-10
x=3+(-10)

y=-10
x=-7

D) x+y=9
x-y=-1

x+y=9
x=-1+y

-1+y+y=9
x=-1+y

2y=9+1
x=-1+y

2y=10/:2
x=-1+y

y=5
x=-1+5

y=5
x=4

D) x+y=8
x-y=0

x=8-y
8-y-y=0

x=8-y
-2y=-8/:(-2)

x=8-y
y=4

x=8-4
y=4

y=4
x=4